Pengaruh Pemberian Sari Kacang Hijau Terhadap Produksi ASI Pada Ibu Menyusui - Mirani, Nanda (Universitas Muhammadiyah Surabaya, 2024)
Objective: Abstract Breast milk (mother's milk) is the only natural food for babies. Insufficient breast milk or low breast milk production is one of the problems in postpartum mothers. So, sometimes, mothers replace their breast milk with formula milk. Mothers with low breast milk production can overcome this problem by consuming green beans because the nutritional content of green beans is relatively high and the consistency is perfect. This study aims to determine the effect of green bean juice on breast milk production in breastfeeding mothers. Methods: This research uses a pre-experimental design with a one-group pretest-posttest design. The population in this study consisted of mothers breastfeeding babies 0-6 months. The sample that will be involved in this research is 16 people, using purposive sampling technique. Data analysis used the Wilcoxon test Results: The results of the study showed an increase in breast milk production as seen from the average frequency of breastfeeding before being given green bean juice, which was 7.06, and after being given green bean juice, it was 10.63. Based on the results of the Wilcoxon statistical test, it was found that the p-value was 0.000 < 0.05, which means there was a difference in breast milk production before and after giving green bean juice to breastfeeding mothers. Conclusion: Pada The conclusion in this study is that giving green bean juice affects breast milk production in breastfeeding mothers. It is hoped that breastfeeding mothers will maintain their nutritional intake, one of which is by consuming green beans, which can be processed into green bean juice, porridge, or green bean juice regularly to increase breast milk production so that later, the baby can grow and develop well.